Glenohumeral stabilizing roles of the scapulohumeral muscles: Implications of muscle geometry. (13th February 2020) - Mulla, Daanish M.; Hodder, Joanne N.; Maly, Monica R.; Lyons, James L.; Keir, Peter J.
Abstract: Dynamic stability provided by muscles is integral for function and integrity of the glenohumeral joint. Although the high degree of inter-individual variation that exists in musculoskeletal geometry is associated with shoulder injuries, there is limited research associating the effects of muscle geometry on the potential stabilizing capacities of shoulder muscles. The purpose of this investigation was to evaluate the stabilizing functions of the scapulohumeral muscles using computational modeling and to quantify the sensitivity of muscle stabilizing roles to changes in muscle geometry. Muscle stability ratios in the superior/inferior and anterior/posterior directions were computed as the ratio between the muscle's shear components relative to compression throughout arm elevation in the scapular plane. Muscle attachment locations on the clavicle, scapula, and humerus were iteratively adjusted using Monte Carlo simulations. Consistent with previous experimental studies, the rotator cuff muscles were identified as the primary stabilizers of the glenohumeral joint; whereas the deltoids and coracobrachialis have a strong potential for superiorly translating the humerus at low elevation angles. Variations in the stability ratios due to altered muscle geometry were muscle- and angle-specific. In general, the highest variation was observed for the subscapularis and deltoids (at low elevation angles), while the remaining rotator cuff muscles largely maintained their capacity to provide compressive stabilizing forces at the glenohumeral joint. Changes in muscle stability ratios may affect dynamic stability of the humerus that could differentially predispose individuals to greater risk for injury.